PENGARUH KEPEMILIKAN INSTITUSIONAL DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - Putri, Atlin Syaqia Syawali; Lasar, Hilary Flora A.T. (E-Jurnal Akuntansi TSM, 2024)
The research aims to obtain empirical evidence of the influence of independent variables such as institutional ownership, profitability, leverage, capital intensity ratio, sales growth and company size on the dependent variable of tax avoidance. The research uses companies in the Consumer Non-Cyclicals and Consumer Cyclicals sectors listed on the Indonesian Stock Exchange for the period 2020 to 2022. The sampling method used in this study was purposive samplings by setting five sample criteria, thus obtaining samples of as many as 58 companies with a total of 174 data. The data analysis method used in this study is the multiple regession method. The results of this research show that the variables profitability, leverage, sales growth and company size have an influence on tax avoidance. Institutional ownership and capital intensity ratio have no influence on tax avoidance.